Particularities of Crohn's disease in pediatric patients: current status and perspectives regarding imaging modalities - Schreiber-Dietrich, Dagmar; Chiorean, Liliana; Cui, Xin-Wu; Braden, Barbara; Kucharzik, Torsten; Juengert, Joerg; Kosiak, Wojciech; Stenzel, Martin; Dietrich, Christoph F. (Expert Review of Gastroenterology and Hepatology, 2015)
A consensus on the best imaging modality evaluating inflammatory bowel disease in the pediatric population is lacking and it is often unclear which modality to choose in specific clinical circumstances. Children with inflammatory bowel disease are exposed to ionizing radiation from multiple imaging studies performed at initial diagnosis, throughout treatment and during the follow-up period. This paper discusses the value of different imaging techniques in pediatric patients with inflammatory bowel disease and gives a review of the literature. In addition, particular features of inflammatory bowel disease in children including the predilection of affected segments in the gastrointestinal tract are highlighted. Based on current literature knowledge, we encourage an integrative approach to the interpretation of clinical and imaging data for diagnosis and follow-up in daily clinical settings.
EVALuna2:18921